Optical and thermal properties of Zn/Al-layered double hydroxide nanocomposite intercalated with sodium dodecyl sulfate - Babakhani, Samaneh; Talib, Zainal Abidin; Hussein, Mohd. Zobir; Ali Ahmed, Abdullah Ahmed (Hindawi Publishing Corporation, 2014)
Zn/Al-LDH-SDS nanocomposites have been prepared using a coprecipitation method in different molar ratio of Zn2+/Al3+ = 2, 3, and 4 at pH = 10 and different concentrations of sodium dodecyl sulfate solution (0.2 M, 0.4 M, and 0.8 M). The XRD and FTIR data show the successful intercalation of SDS into the LDH interlayer. The XRD diffractogram showed that the basal spacing for is 0.89 nm compared to 2.54–2.61 nm for the Zn/Al-SDS nanocomposite. Optical band gap of the samples was calculated using Kubelka-Munk model. Due to the presence of LDH phase, two band gap energies ( and ) were observed. The values of and were found around 4.8 eV and 3.75 eV for Zn/Al-LDH (r = 2, 3, and 4). The values of band gap of LDH-SDS nanocomposites were found to increase to around 4.2 eV and 5.2 eV. For Zn4Al-LDH-SDS with 0.4 M and 0.8 M of SDS, only one energy gap at around 3.23 eV was observed. The optical band gap of phase increased as the amount of SDS increases. Thermal diffusivity of the resulted nanocomposite was also investigated.